2022
DOI: 10.1186/s13024-022-00542-y
|View full text |Cite
|
Sign up to set email alerts
|

TREM2 in the pathogenesis of AD: a lipid metabolism regulator and potential metabolic therapeutic target

Abstract: Triggering receptor expressed on myeloid cells 2 (TREM2) is a single-pass transmembrane immune receptor that is mainly expressed on microglia in the brain and macrophages in the periphery. Recent studies have identified TREM2 as a risk factor for Alzheimer’s disease (AD). Increasing evidence has shown that TREM2 can affect lipid metabolism both in the central nervous system (CNS) and in the periphery. In the CNS, TREM2 affects the metabolism of cholesterol, myelin, and phospholipids and promotes the transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 206 publications
0
21
0
Order By: Relevance
“…A previous experimental study identified Trem2 and Tyrobp as significant hub genes in TBI mice expressing human APOE [62]. Trem2 is an innate immune receptor mainly expressed on various tissue macrophages, such as microglia in the brain [63]. It transmits intracellular signals through binding with the adaptor protein Tyrobp, which in turn regulates many crucial biological processes, including phagocytosis, chemotaxis, inflammatory responses, and lipid metabolism [56,63,64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous experimental study identified Trem2 and Tyrobp as significant hub genes in TBI mice expressing human APOE [62]. Trem2 is an innate immune receptor mainly expressed on various tissue macrophages, such as microglia in the brain [63]. It transmits intracellular signals through binding with the adaptor protein Tyrobp, which in turn regulates many crucial biological processes, including phagocytosis, chemotaxis, inflammatory responses, and lipid metabolism [56,63,64].…”
Section: Discussionmentioning
confidence: 99%
“…Trem2 is an innate immune receptor mainly expressed on various tissue macrophages, such as microglia in the brain [63]. It transmits intracellular signals through binding with the adaptor protein Tyrobp, which in turn regulates many crucial biological processes, including phagocytosis, chemotaxis, inflammatory responses, and lipid metabolism [56,63,64]. It was reported that Trem2 deficiency alleviated the acute peripheral macrophage infiltration and attenuated chronic hippocampal atrophy and cognitive deficits in a murine TBI model [65].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, two populations with distinct ontogenies expressing a lipid-associated phenotype were observed. Both express high levels of TREM2 , which has been linked to systemic metabolism and adipose tissue function (62) and has emerged as a marker of pro-tumorigenic macrophages (63) .…”
Section: Discussionmentioning
confidence: 99%
“…TREM2 is a receptor that is selectively expressed on microglia in the brain (Wang et al, 2015 ; Ulland et al, 2017 ; Nugent et al, 2020 ) and macrophages in the periphery (Chung et al, 2002 ), and is known to play a role in inflammatory signaling (Kobayashi et al, 2016 ), microglial metabolism (Ulland et al, 2017 ), phagocytosis (Poliani et al, 2015 ; Wang et al, 2015 ), activation (Jay et al, 2015 ; Wang et al, 2015 ), survival (Wang et al, 2015 ; Ulland et al, 2017 ; Zheng et al, 2017 ), and proliferation (Poliani et al, 2015 ). TREM2 was identified as a lipid receptor and was shown to control cholesterol and phospholipid metabolism in the brain (Wang et al, 2015 ; Andreone et al, 2020 ; Nugent et al, 2020 ; Li et al, 2022 ). Lipidated CLU can bind to Aβ, and CLU-Aβ complexes can then be taken up by microglia through binding to TREM2 (Yeh et al, 2016 ).…”
Section: Clu Function In Admentioning
confidence: 99%
“…This suggests that CLU may be facilitating microglial Aβ uptake through TREM2 ( Figure 1 ), and a lack of sCLU due to changes in CLU isoform expression may affect Aβ uptake and clearance. In addition, given the role that lipid metabolism plays in AD (Zhu et al, 2019 ; Kao et al, 2020 ; Paasila et al, 2021 ; Turri et al, 2022 ), TREM2 function as a lipid metabolism regulator (Wang et al, 2015 ; Nugent et al, 2020 ; Li et al, 2022 ), and CLU binding lipids and cholesterol to influence their trafficking (Matukumalli et al, 2017 ; Foster et al, 2019 ), the interaction between TREM2 and CLU should be further explored as it could have a great impact on AD pathogenesis.…”
Section: Clu Function In Admentioning
confidence: 99%